1971
DOI: 10.1063/1.1676181
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Collision-Induced Absorption in CO2. I. Temperature Dependence

Abstract: Accurate measurements of collision-induced absorption in CO2 are made at a number of temperatures in the range from − 40 to 60°C in the wavelength region 7–250 cm−1. Direct evidence for the separation of the pure translational band from the rotational–translational band is obtained at all temperatures. This and other aspects of the band shape are discussed. Over the entire temperature range, the experimentally determined Kramers–Kronig integral is found to be in good agreement with the theoretical value, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…This is illustrated in figure 5, which shows the continuum profiles (plotted on the linear Y -scale) together with the CIA/dimer spectra of carbon dioxide (except for the allowed n 2 fundamental band) [29,30] and the CIA spectra of nitrogen [31,32]. We assume that the compared spectra have the same physical origin.…”
Section: On the Continuum Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated in figure 5, which shows the continuum profiles (plotted on the linear Y -scale) together with the CIA/dimer spectra of carbon dioxide (except for the allowed n 2 fundamental band) [29,30] and the CIA spectra of nitrogen [31,32]. We assume that the compared spectra have the same physical origin.…”
Section: On the Continuum Interpretationmentioning
confidence: 99%
“…For a dipolar molecule, such as H 2 O, those processes may lead to enforced acts of absorption and/or emission. N 2 roto-translational band [29] collision-induced and dimer absorption profiles in the v 1 , 2v 2 region [28] nitrogen CIA profile in the vibrational fundamental band region [30] 230 K 270 K 346 K CIA bands of dipole-less molecules are well known and quite well studied experimentally (see Frommhold [28]). The fact that molecular collisions produce absorption in regions of forbidden transitions is very important.…”
Section: On the Continuum Interpretationmentioning
confidence: 99%
“…The absorption from these bands has been parameterized by the method used by Pollack et al (1980) based on measurements reported by Ho et al (1971), Moore (1971), andG. Birnbaum (private communication, 1979).…”
Section: = F(t) [In (A)] 1/(as)mentioning
confidence: 99%
“…The electric dipole moment of CH 3 CN is predicted to be 3.95 debye, while experimenting gives 3.92 debye [41 ]. Values for the C0 2 experimental quadrupole moment [42][43][44][45] vary between -1.34 and 1.5 x 10~1 9 coulomb Ä 2 , while the calculated value lies at the upper end of this range with a value of -1.514 x 10" 19 coulomb Ä 2 . Table 3 compares the S APT components computed using the MC+BS described in section 3 with the equivalent DCBS at the two geometries Gl and G4.…”
Section: Resultsmentioning
confidence: 99%